Groundwater Aquifer Analysis Using the Schlumberger Configuration Vertical Electrical Sounding Resistivity Method with Dar Zarrouk Parameters in the Komplek Perkantoran Gunung Merah Sentani - Kareth, Zakaria Victor; Flassy, Reinhard V. (Jurnal Fisika Papua, 2025)
A study has been conducted using the Vertical Electrical Sounding (VES) method of Schlumberger configuration and Dar Zarrouk parameters which aims to determine the range of resistivity values of the subsurface layer, the depth of the groundwater aquifer layer, the thickness of the water aquifer layer and the range of Dar Zarrouk parameter values at the research site. The research location is in the office complex of Gunung Merah Sentani, Jayapura Regency as many as four sounding points with a maximum length of 175-300 meters. The results of this research show that the VES 1 point has two aquifer layers with a depth range of 4 - 7 meters and 14-31 meters. which is a fragment of Gneiss rock containing sand, gravel and clay. The resistivity values ​​of each aquifer layer are 26-45 Ωm and 16 Ωm respectively. At VES point 2, the inversion model parameters show that there are three aquifer layers in the depth range of 2 - 4 meters, 7 - 13 meters and 30 - 91 meters. And the resistivity values ​​of each aquifer are 6, 13 and 35 Ωm. At VES point 3, the inversion model parameters show that there are two aquifer layers in the depth range of 5 - 16 meters and 25 - 66 meters with resistivity values ​​for each aquifer layer of 15 and 22 Ωm respectively. At VES point 4, the inversion model parameters show that there are two aquifer layers in the depth range of 3 - 5 meters and 7 - 20 meters with the resistivity values ​​for each aquifer layer being 24 and 7 Ωm respectively.